„I understand life as the Cry of some Voice...“: Correspondence between Sigitas Geda and Kornelijus Platelis (1977–1981) - Kmita, Rimantas (Literatūra, 2022)
The publication presents the correspondence between the poets Sigitas Geda (1943–2008) and Kornelijaus Platelis (b. 1951) in letters in 1977–1981. The publication was prepared with letters from that period found in the personal archives of Uršulė Gedaitė and Kornelijus Platelis. The 13 letters from the late 1970s and early 1980s show the moods of the stagnation years, the hesitations of people in culture, and the reflections on the meaning of creation in the atmosphere of Soviet stagnation. Compared to Geda‘s other known letters, those written to Platelis are characterised by a closer and more open relationship with the addressee. They contain the most important and quite intimate reflections on the creative process, as well as frank evaluations of colleagues‘ works, which differ from those we read in published reviews or journalism.